ความสัมพันธ์ระหว่างคุณลักษณะของงาน ความฉลาดทางอารมณ์ กับความสามารถในการปฎิบัติงานของพยาบาลวิชาชีพ ศูนย์สุขภาพชุมชน ภาคเหนือตอนล่าง - นลินี เกิดประสงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The descriptive research was designed to study the relationships among job characteristics, emotional quotient, and job performance of professional nurses in primary care units, lower northern region. The sample were 220 professional nurses who were located in primary care units, lower northern region. Subjects were selected using a stratified random sampling technique. Research instruments were the proactive job characteristics questionnaire, emotional quotient questionnaire, and job performance of professional nurse in primary care unit questionnaire. All questionnaires were tested for validity and reliability. Cronbachs alpha reliability coefficients for the three instruments were .89, .93, and .83 respectively. The data were analyzed by frequencies, percentage, mean, standard deviation and Pearsons product moment correlation coefficients. Major findings were as follows: 1. Mean of job performance of professional nurses in primary care units, lower northern region were at the high level ([Mean] = 3.41, S.D = .29, ). 2. There were significant positive relationships between job characteristics and job performance ( r = .25, p = .05) and between emotional quotient and job performance (r = .34, p = .05).